Using a Reading Journal to Develop Source Use Competencies for Academic Writing [Abstract] - Anderson, Rheanne; Molyneux, Elizabeth (M. Narikbayev KAZGUU University, Nazarbayev University, 2019)
Appropriate incorporation of source material in academic writing can be challenging for university students, and those who struggle to demonstrate competency in this area can run into issues with plagiarism. Pedagogic approaches to reducing plagiarism often take the complementary routes of explicit teaching on academic integrity combined with instruction on source use and referencing (Pecorari and Petric, 2014). This presentation will describe an instructional tool used in an Academic Reading course on a pre-Masters program for students entering an EMI university in Kazakhstan.
Keywords: The 4th Annual International Conference on Academic Integrity; academic integrity; academic writing; plagiarism pedagogy